MODERN METHODS OF TEACHING ENGLISH: FROM TRADITIONAL TO INNOVATIVE APPROACHES - Amanullaeva Kamola Muminovna; Mukhiddinva Komila Gafurjonovna (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract:  This  article  explores  the  evolution  of  English  language  teaching methods, from traditional to innovative approaches. Particular attention is given to the analysis of grammar-translation, direct, audio-lingual, communicative, and reading-based methods, as well as author-developed approaches tailored to individual learner needs.  The  role  of  information  technologies  in  transforming  language  education  is highlighted, emphasizing their contribution to personalization and interactivity. Based on comparative analysis, the article offers recommendations for effectively combining classical  and  modern  methodologies  to  enhance  English  language  teaching  in  the context of globalization and digitalization in education.